The Practice of Intolerance by the Alberta Social Credit Government and the Growth of Jewish Activism Between 1943 and 1968 - Rohfritsch, Jason (Université d'Ottawa / University of Ottawa, 2025)
The following thesis paper examines the continued presence of antisemitism in the ruling Alberta Social Credit Party (SCP) between 1943 and 1968, and Canadian Jewish organizational efforts to obtain anti-discrimination legislation. The Alberta Social Credit grassroots movement involved radical monetary policies, religious fundamentalism, conspiracy theories and antisemitic rhetoric. How did such an unorthodox party retain provincial control for thirty-six years despite the organization's persistent antisemitism? The question is significant to the ongoing narrative of Alberta politics amid a sharp rise in antisemitism within Canada today. The principal methodology includes qualitative research of primary sources from the SCP and Canadian Jewish archives and academic literature. Within this study period, the Canadian Jewish Congress (CJC) transitioned from an organization with little infrastructure to a leading institution with strong ties to other Canadian Jewish bodies, and labour and civil groups, struggling to enshrine protections for Canadian Jews. The results demonstrate that in the 1950s and early 1960s, as many Canadian provincial governments enacted equal rights legislation, Premier Ernest Manning's Social Credit government resisted such laws in Alberta. As a result, Jewish leaders escalated initiatives in Alberta. Throughout his leadership, Manning routinely denied accusations of antisemitism leveled against his party. Eventually, Manning and the Alberta SCP government were forced to establish human rights legislation in 1966, although the provisions were limited in scope. Manning curtailed Social Credit antisemitism when it became a political liability, but he did not comprehensively eliminate it. Through collaborative efforts, the CJC and other Canadian Jewish groups finally achieved legalized protections for the Jewish community in Alberta.
Keywords: Alberta Social Credit Party; Canadian Jewish Congress; Antisemitism